Technological aspects of restoring railway wheelsets, methods for improving efficiency - S.O. Bakhman (Технічна інженерія, 2025)
Modern industry and transport industry are impossible without the use of technological methods and means of restoring the operational characteristics of equipment. Railway transport enterprises have recently paid considerable attention to the development and implementation of resource-saving and environmentally friendly technologies for the repair and restoration of rolling stock components. One of the new directions in this area is the combination of high-quality surface preparation using innovative resource-saving technologies, such as surfacing [1].